Standardization Of Bali Bull Cattle Based on Indonesia National Standard at Baturiti Artificial Insemination Center - P. P. Y., Hendriana; Sumardani, N. L. G; Mariani, N. P. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the standardization of bali bull at baturiti artificial insemination center. Primary data is obtained from technical surveys, interviews, and job training, while secondary data is obtained from the records of parameter measurements in bali bull on the October 2018 schedule at baturiti artificial insemination center. The variables observed in Student Internship include: the origin of the bull, the health condition of bali bull, the qualitative appearance of feather color, and the shape of the head, as well as quantitative individuals in the high of gumba (HG), body length (BL), chest circumference (CC), scrotum circumference (SC), and body weight (BW). The obsevations are that the origin of bali bull has been recorded, the condition is healthy, the qualitative appearance is good, quantitative appearance of bali bull studs according to SNI except bali bull with code 11240 with a scrotum circumference of 25 cm below the SNI standard of 26 cm for ages > 24-36 months. Student Work Practice Results can be concluded that in general Bali bull at at baturiti artificial insemination center in Bali meet SNI standards, namely the origin of studs is clear, bull health conditions in general are healthy, qualitative and quantitative appearance of bali bull studs according to SNI except bali cattle with code 11240 with a scrotum circumference of 25 cm below the SNI standard of 26 cm for ages > 24-36 months. Keywords: Standardization, bali bull Cattle, Qualitative Performams, Quantitative Individual